The Influence of Corporate Ethical Identity on the Saving Interest of Customers at BMT UGT Nusantara Arosbaya - Marom, Aufal; Arif, Zainul (STAI Syaichona Moh. Cholil Bangkalan, 2025)
This study aims to analyse the influence of Corporate Ethical Identity (CEI) on the saving interest of customers at BMT UGT Nusantara Arosbaya. The research uses a quantitative approach with a causal design. The population consists of 1,094 customers, with 66 respondents selected using purposive sampling. Data were collected through closed-ended questionnaires with a five-point Likert scale and analysed using simple linear regression. The results indicate that CEI has a significant influence on saving interest, explaining 84.7% of the variance in saving interest. This finding highlights the importance of strengthening the corporate ethical identity in building trust and customer loyalty in Islamic financial institutions. The study contributes to the development of strategies for managing customer relationships based on ethical values in Islamic financial institutions.